Early weaning of twin-born lambs onto a herb-clover mix containing plantain (Plantago lanceolata), chicory (Cichorium intybus), red clover (Trifolium pratense) and white clover (Trifolium repens) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science, Massey University, Palmerston North, New Zealand - Ekanayake, Lukshman (Massey University, 2020)
Early weaning of lambs may be a useful management tool when either herbage quality, or quantity, limits lamb growth. Herb-clover mixes containing chicory, plantain, red clover and white clover have been shown to improve the growth of suckling lambs and those weaned at a traditional age compared to ryegrass-clover based pastures. The objectives of this thesis were to examine; 1) the effect of lamb live weight at early weaning on their subsequent growth on a herb-clover mix; 2) the response of early weaning of lambs onto a herb-clover mix when ryegrass-clover based pasture herbage masses were restricted rather than 𝘢𝘥-𝘭𝘪𝘣𝘪𝘵𝘶𝘮; 3) the effect of weaning lambs at different minimum live weights (16 kg then 14 kg); 4) the impact of early exposure of lambs to a herb-clover mix prior to early weaning on their growth post weaning, and 5) to characterise the nutritional composition of the herb-clover mix during the late spring to autumn period. Lambs weaned early onto a herb-clover mix, at a minimum weight of 16 kg at approximately 50 days of age, had the potential to grow at a similar rate to unweaned lambs on a ryegrass clover based pasture. This was more apparent when herb-clover mix had a high chicory (57%) and clover content (14%) or there was a low (< 5%) clover content in the ryegrass-clover based pasture. In first year of the study light lambs (< 18 kg) grew 50 g/day slower than heavy lambs (18-23 kg), however, in the second year they grew at a similar rate . Weaning lambs less than 16 kg onto a herb-clover mix, therefore, should be undertaken with caution. Further, the advantages of early weaning were enhanced when the supply ryegrass-clover based pasture resulted in restricted intake of ewes and lambs (< 1200 kg DM/ha). Lambs weaned at a minimum weight of 14 kg at approximately 40 days of age, were found to grow at a similar rate to unweaned lambs on a ryegrass-clover based pasture. Early exposure to a herb-clover mix prior to early weaning had no impact on subsequent growth of early-weaned lambs.
Keywords: Lambs; Feeding and feeds; New Zealand; Weight; Growth; 300303 Animal nutrition